2020
DOI: 10.2174/1381612826666200122153541
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and Alcohol Use Disorder: Are Psychobiotics a Novel Therapeutic Strategy?

Abstract: In recent years, there has been an exciting focus of research attempting to understand neuropsychiatric disorders from a holistic perspective in order to determine the role of gut microbiota in the aetiology and pathogenesis of such disorders. Thus, the possible therapeutic benefits of targeting gut microbiota are being explored for conditions such as stress, depression or schizophrenia. Growing evidence indicates that there is bidirectional communication between gut microbiota and the brain that has an effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 157 publications
0
12
0
Order By: Relevance
“…There also is a definite need to study the evolution of AUD patients’ EF patterns throughout the course of abstinence and to explore possible predictors of EF subgroups in AUD. Important candidate variables that are likely predictors of AUD patients’ EF patterns include genetic variations (Chart ier et al, 2017), cerebral structure and functionality (Goldstein and Volkow, 2002), psychiatric comorbidities, especially symptoms of anxiety and depression (Schuckit, 2006), nutritional deficiency (Gautron et al, 2018), or even the characteristics of the gut microbiota (Rodriguez‐Gonzalez and Orio, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…There also is a definite need to study the evolution of AUD patients’ EF patterns throughout the course of abstinence and to explore possible predictors of EF subgroups in AUD. Important candidate variables that are likely predictors of AUD patients’ EF patterns include genetic variations (Chart ier et al, 2017), cerebral structure and functionality (Goldstein and Volkow, 2002), psychiatric comorbidities, especially symptoms of anxiety and depression (Schuckit, 2006), nutritional deficiency (Gautron et al, 2018), or even the characteristics of the gut microbiota (Rodriguez‐Gonzalez and Orio, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that the gut microbiome can carry sufficient metabologenomic information to produce alcohol dependency. Furthermore, other researchers have suggested that psychobiotics (probiotic bacteria affecting brain function and neurochemical balance) could represent a useful therapeutic strategy for alcohol use disorder [135].…”
Section: Who Behavior Modifications #2 and #3: Consume Less Alcohol And Stop Using Tobacco -(In Spite Of The Microbiome's Role In Addictimentioning
confidence: 99%
“…Thus, alcohol-induced changes in the gut microbiota may contribute not only to development of alcoholic liver disease, but also to a variety of CNS disorders (Engen et al 2015 ; García-Cabrerizo et al 2021 ). Indeed, it has been suggested that use of probiotic might be of potential use in prevention and treatment of alcohol-associated pathologies (Engen et al 2015 ; Lowe et al 2018 ; Rodriguez-Gonzalez and Orio 2020 ; Carbia et al 2021 ; Gupta et al 2021 ). In this regard, it was recently reported that butyrate (BUT) ameliorates alcoholic fatty liver disease in mice (Zhang et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%